Cyclin D1 differential activation and its prognostic impact in patients with advanced breast cancer treated with trastuzumab. Issue 2 (12th May 2019) - Mountzios, G; Kotoula, Vassiliki; Kolliou, Georgia-Angeliki; Papadopoulou, Kyriaki; Lazaridis, Georgios; Christodoulou, Christos; Pentheroudakis, George; Skondra, Maria; Koutras, Angelos; Linardou, Helena; Razis, Evangelia; Papakostas, Pavlos; et al.
Abstract : Introduction: We sought to determine the level of activation of the critical components of the cyclin D1-mediated pathway and to evaluate their prognostic significance across the different molecular subtypes of advanced breast cancer. Patients and methods: The study population comprised 219 female patients with advanced breast cancer who had been found to have human epidermal growth factor receptor 2 (HER2)-positive disease by local testing and were all treated with trastuzumab-based regimens. For all tumours, central testing for HER2 was performed, and cyclin D1 gene ( CCND1 ) amplification, mRNA and protein expression were assessed by FISH, quantitative real-time-PCR and immunohistochemistry, respectively. Prognostic impact on clinical endpoints was evaluated with Cox regression analyses. Results: After central testing, only 134 (61.2%) of 219 patients were confirmed to have HER2 gene amplification by FISH and/or 3+ HER2 protein expression by immunohistochemistry. After a median follow-up time of 136.0 months (95% CI 123.3 to 148.9), 105 (78.4%) HER2-positive patients and 76 (89.4%) HER2-negative patients had died, while 80% of the former and 87.1% of the latter had experienced a disease relapse. Patients with positive oestrogen receptor/progesterone receptor status presented with higher cyclin D1 mRNA expression. In the HER2-negative subgroup, patients with negative cyclin D1 protein expression were at higher risk of progression (HR= 1.66, 95%CI 1.01 to 2.72, Wald's p=0.045). Among de novo metastatic patients, the risk of progression was higher for patients with non-amplified CCND1 tumours (HR= 2.00, 95% CI 1.03 to 3.90, p=0.041). Conclusion: Aberrant activation of the cyclin D1-mediated pathway appears to reduce the risk of progression in HER2-negative tumours, but not in HER2-positive ones.